Numerical analysis of ELM stability with rotation and ion diamagnetic drift effects in JET. (11th September 2017) - Aiba, N.; Giroud, C.; Honda, M.; Delabie, E.; Saarelma, S.; Frassinetti, L.; Lupelli, I.; Casson, F.J.; Pamela, S.; Urano, H.; Maggi, C.F.
Abstract: Stability to the type-I edge localized mode (ELM) in JET plasmas was investigated numerically by analyzing the stability to a peeling-ballooning mode with the effects of plasma rotation and ion diamagnetic drift. The numerical analysis was performed by solving the extended Frieman–Rotenberg equation with the MINERVA-DI code. To take into account these effects in the stability analysis self-consistently, the procedure of JET equilibrium reconstruction was updated to include the profiles of ion temperature and toroidal rotation, which are determined based on the measurement data in experiments. With the new procedure and MINERVA-DI, it was identified that the stability analysis including the rotation effect can explain the ELM trigger condition in JET with ITER like wall (JET-ILW), though the stability in JET with carbon wall (JET-C) is hardly affected by rotation. The key difference is that the rotation shear in JET-ILW plasmas analyzed in this study is larger than that in JET-C ones, the shear which enhances the dynamic pressure destabilizing a peeling-ballooning mode. In addition, the increase of the toroidal mode number of the unstable MHD mode determining the ELM trigger condition is also important when the plasma density is high in JET-ILW. Though such modes with high toroidal mode number are strongly stabilized by the ion diamagnetic drift effect, it was found that plasma rotation can sometimes overcome this stabilizing effect and destabilizes the peeling-ballooning modes in JET-ILW.